A contribuição da fábrica de software e de seus produtos para o processo de flexibilização organizacional na empresa cliente - Almeida, Risoleide de Freitas (2009)
The technological development, mainly those relatives to information technology and telecommunications, made hard changes into organizations and into the society at ali, they are issue of entreprises conflicts, due the changing they make in the society's life and in the way to work now. This study looks for analyse the part of IT, slecially the softwares, in the discussion to the changing for the fordist model to the post fordist one. Adopting these Technologies may be an essencial competency and great competitivity factor to the company, in stead of these new entreprise dynamic's impacts, wich uses massively the IT need more studies and comprehension in order to verify if into this dymanic is envolved na effective process of flexibilization or if it is merally cost reduction sistematic. This work was based on case study, through searching done with software's customers, in great enterprise of electrical sector, looking for to verify these producfs contribution in the flexibilization process. The results show that exist factors which make easy the flexibilizations process, based in the softwares siystems. The softwares hardly change the communication process, mainly between the differents leveis into the hierarchy. However this technology is not yet used as resource to make the job relations more flexibles, specially when we see the activities in non conventionals places and schedules. In order to do flexible management model, with post fordists charachter, it's necessary to develop new profile in the job relations, which has fordist production character yet.